ANALISIS PEMIKIRAN EKONOMI AL-GHAZALI - Adelia, Putri; Khoiriyah , Zainab (Journal of Management, Economic and Accounting (JMEA), 2025)
According to al-Ghazali, the goal of a Muslim's life is to attain Allah's blessings (ridha) both in this world and the next. One of the means that facilitates this achievement is legal wealth (halal) in economic activities. For al-Ghazali, the market is believed to be an evolution of "natural law," namely, the desire that comes from within each individual to fulfill their economic needs. With his evolutionary theory of money, al-Ghazali explains that there has been a shift away from barter.